Diversidade, clonagem e caracterização de nucleases extracelulares de Aeromonas spp. - Zacaria, Jucimar (My University, 2017)
Aeromonas spp. are Gram-negative bacteria generally associated to aquatic ecosystems. These bacterial are considered opportunistic pathogens of various animals, including man. Some species of this genus can secrete a wide variety of extracellular enzymes, such as, β-lactamases, lipases, amylases, proteases, nucleases, among others. Nucleases can play multiple roles related to metabolism, protection against exogenous genetic material and, in some cases, virulence factor. In this context, the aim of this study was to evaluate the differences in extracellular DNases activities and electrophoretic profiles between species and isolates of Aeromonas spp., cloning and heterologous expression of nucleases, effect of physical/chemical factors on the enzyme activity, evaluation of nuc, dns and aha3441 expression, and bioinformatics analysis of DNases Dns and Aha3441. The results showed a wide variation in intra- and interspecific DNases extracellular activity, without significant difference between clinical and environmental isolates. DNase zymograms of Aeromonas spp. isolates, using DNA as a substrate, allowed the identification of different DNase activity profiles. A total of six bands of apparent molecular mass ranging between 22 and 119 KDa were identified. Bands of 22 and 85 KDa were the most frequent among Aeromonas spp. isolates analyzed. The Dnases secreted by Aeromonas hydrophila IBAer119 are affected by the action of proteases produced by the isolate itself. The evaluation of dns, aha3441 and nuc gene expression of A. hydrophila IBAer119 allowed observing high transcription rates for dns and aha3441 genes, which coincide with the peak of extracellular DNase activity. Extracellular DNases identified in isolated A. hydrophila IBAer119 do not play preferably a nutritional role, indicating that its function can be related to protection against exogenous DNA or virulence. The enzymes Dns and Aha3441 from A. hydrophila IBAer119 were cloned and heterologously expressed in Escherichia coli DH5α. Both DNases uses Mg as a cofactor and are inhibited by EDTA and SDS. Experimental data indicates that Dns and Aha3441 have maximal activity at pHs between 7.0 and 9.0, and temperatures between 37°C and 60°C, for Dns, and between 37°C and 50°C, for Aha3441. Both enzymes exhibited high thermal stability when kept at 40°C for 50 minutes. Dns and Aha3441 showed ability to degrade RNA and DNA characterizing them as sugar non-specific nucleases. The sequence analysis of the protein identified the presence of a signal peptide with 20aa, for Dns enzyme, and 23aa, for Aha3441 enzyme, indicating that these enzymes are secreted by secII system. Moreover, the bioinformatics evaluation of the Dns allowed identifying an Endonuclease I superfamily domain, and with high similarity with DNases of the others bacterial genera. DNase Aha3441 has an EEP superfamily domain and OB subfamily folds, similar to those observed in another Aeromonas DNase called Nuc. The threedimensional model of Dns indicates the presence a catalytic site with ββα-metal topology, typical of other endonucleases. The three-dimensional model of Aha3441 showed high conformational similarity with the D chain of the BP DNase I (bovine pancreatic DNase). In addition, the metal binding, the phosphate binding, and the catalytic sites of Aha3441 showed high degree of conservation when compared with homologs of other bacteria, and even BP DNase I, indicating that Aha3441 shares the same mechanism of action.
Aeromonas spp. são bactérias Gram-negativas relacionadas, principalmente, a ecossistemas aquáticos. Estas bactérias são consideradas patógenos oportunistas de diversos animais, inclusive o homem. Algumas espécies gênero Aeromonas secretam uma ampla variedade de enzimas extracelulares, dentre elas β-lactamases, lípases, amilases, proteases, e nucleases entre outras. As nucleases podem desempenhar múltiplos papéis relacionados ao metabolismo, à proteção contra a entrada de material genético exógeno e, em alguns casos, como fator de virulência. Neste contexto, o objetivo deste trabalho foi avaliar as diferenças nas atividades de DNases extracelulares e o perfil eletroforético entre espécies e isolados do gênero Aeromonas; a clonagem e expressão heteróloga, caracterização frente a fatores físicos/químicos que afetam a atividade enzimática e análise de bioinformática das DNases Dns e Aha3441, bem como a avaliação da expressão dos gene nuc, dns e aha3441 de Aeromonas hydrophila IBAer119. Os resultados mostraram uma ampla variação intra e interespecífica na atividade de DNases extracelulares, sem diferença significativa entre isolados clínicos e ambientais. Zimogramas dos isolados de Aeromonas spp., empregando DNA como substrato, possibilitaram a identificação de diferentes perfis de atividade DNásica. Um total de seis bandas de massa molecular aparente variando entre 22 e 119 KDa foram identificadas. As bandas de 22 e 85 KDa foram as mais frequentes entre os isolados de Aeromonas spp. analisados. As DNases secretadas por A. hydrophila IBAer119 são afetadas pela ação de proteases produzidas pelo próprio isolado. A avaliação da expressão dos genes dns, aha3441 e nuc de A. hydrophila IBAer119 permitiu observar maiores taxas transcricionais para os genes dns e aha3441, as quais, coincidem com o pico de atividade DNásica extracelular. As DNases extracelulares identificadas no isolado de A. hydrophila IBAer119 não desempenham preferencialmente, um papel nutricional, sugerindo que sua função pode estar relacionada à proteção contra entrada de DNA exógeno ou à virulência. As enzimas Dns e Aha3441 provenientes de A. hydrophila IBAer119 foram clonadas e expressas de forma heteróloga em Escherichia coli DH5α. Ambas DNases utilizam Mg como co-fator e são inibidas por EDTA e SDS. A avaliação permitiu observar que Dns e Aha3441 apresentam pHs de ação entre 7,0 e 9,0 e temperaturas de atividade entre 37°C e 60°C, para Dns, e temperaturas de atividade entre 37°C e 50°C, para Aha3441. Ambas DNases apresentam elevada estabilidade térmica quando mantidas a 40°C por até 50 minutos. Tanto Dns quanto Aha3441 apresentaram capacidade de degradar RNA e DNA sendo assim caracterizadas como nucleases açúcar não especificas. A análise da sequência proteica permitiu identificar a presença de um peptídeo sinal de 20aa para a enzima Dns e 23aa para a enzima Aha3441, indicando que estas enzima são secretadas por sistema secII. Além disso, a avaliação de bioinformática permitiu identificar que Dns apresenta um domínio correspondente à superfamília da Endonuclease I e apresenta elevado grau de similaridade com DNases de outros gêneros bacterianos. Já a DNase Aha3441 apresenta domínios correspondentes à superfamília EEP e a subfamília OB folds, similares aos observados em outra DNase de Aeromonas spp. denominada Nuc. O modelo tridimensional de Dns permitiu observar a presença de um sítio catalítico com topologia ββα-metal, típico de outras endonucleases. Já o modelo tridimensional de Aha3441 permitiu observar uma elevada similaridade conformacional com a cadeia D da DNase pancreática bovina (BP DNase I). Além disso, os sítios de ligação a metais, sítios de ligação a fosfato e sítio catalítico apresentam elevado grau de conservação quando comparados com homólogos encontrados em outras bactérias e mesmo em relação à BP DNase I, indicando que Aha3441 compartilha o mesmo mecanismo de ação.
Keywords: Aeromonas; Enzimas extracelulares; Biotecnologia; Extracellular enzymes; Biotechnology